Carcinoma of the thyroid gland in childhood - Eckstein, Herbert B.; Tatman, Neclâ (The Turkish Journal of Pediatrics, 1961)
Carcinoma of the thyroid gland is an uncommon disease in childhood. The literature is reviewed briefly and the salient points are stressed; it would appear that most cases present originally with a swelling in the neck. A case presenting with severe tracheal compression is reported, this being the second case to be described in Turkey of carcinoma of the thyroid gland in a child.